Analysis of the Social Value of Cangget Dance as a Cultural Heritage in Metro City, Lampung - Ratna Sari; Karsiwan Karsiwan (UNIVERSITAS MUHAMMADIYAH METRO, 2027)
Cangget Dance is a cultural heritage of the Lampung people, which has important social values, such as cooperation, togetherness, and solidarity. The study aims to analyze how these values ​​become the philosophical foundation in the development of the social life of the Lampung people. The research method used is qualitative with an ethnographic approach, which allows researchers to understand in depth the social values ​​contained in the Cangget Dance. Data collection was carried out through interviews and observations with several residents and youth who are indigenous Lampung people. Based on the results of the study, it was found that the Cangget Dance is used in sacred Lampung traditional events. The philosophical basis is rooted in the social structure and respect for Lampung customs. In addition, the social values ​​contained in the Cangget Dance include order and harmony of the Lampung people in applying social values, especially in the interests of traditional events.